Studi Optimasi Alokasi Produksi Minyak Bumi pada Suatu Wilayah Operasi di Wilayah Kalimantan Timur - Nugroho Marsiyanto; Dieskha Bilqis Jannah (LPPM Institut Teknologi Petroleum Balongan, 2025)
This study aims to optimize oil production allocation in an upstream field in East Kalimantan, where significant deviations of 12–15% were observed between actual and theoretical results exceeding the industry tolerance of 5–10%. The approach uses Nodal Analysis to model well performance based on historical production data, pressure, and fluid properties. To improve accuracy, a BS&W (Basic Sediment and Water) correction factor is introduced to account for variations in fluid composition, which often lead to miscalculations in clean oil volumes. By applying these corrections to back allocation calculations, the model yields more accurate estimates of each well's contribution. The study also addresses operational limitations, such as the absence of test separators and limited personnel, which reduce well testing reliability. Results show that this combined method significantly reduces deviation—sometimes below 10%—without requiring additional infrastructure. It offers a practical, low-cost solution that can be applied in similar field conditions to enhance allocation accuracy.